European funds at the level of the Spanish autonomous communities: Is administrative communication discouraging open innovation? - Marta Martín-Llaguno; María J. Vilaplana-Aparicio; Isabel Gandía-Solera (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Spain is at the bottom in the absorption of European funds, and there is a need to research why. This paper starts from the idea that the problem could, among other issues, be related to the ineffectiveness of administrative communication, both in terms of transparency and dissemination. These dimensions are key for the innovation and open government principles endorsed by the better regulation initiative of the EU and have hardly been studied in this respect by academics. For the period 2021-2027, Spain will receive more than 34,692 million euros from the ERDF and ESF+ funds. The autonomous communities and cities must report on this aid based on communication plans and strategies for the operational programs. After compiling them, assessing their ease of access and analyzing some of their characteristics, such as the levels of execution of their budgets, this research analyzes how the 19 official websites inform about the ERDF and ESF. In several cases, the results point to inefficient institutional management of budgets for communication, as well as obstacles to accessing online content, which is key to transparency. The extent to which these shortcomings may be related to the lack of demand for European funding could be analyzed in future studies.
Keywords: 650; communication; dissemination; ERDF; ESF; EU; grants; public funds; Spain